Colletotrichum species causing grape ripe rot disease in Vitis labrusca and V. vinifera varieties in the highlands of southern Brazil. (19th July 2020) - Echeverrigaray, Sergio; Scariot, Fernando J.; Fontanella, Gabrielli; Favaron, Francesco; Sella, Luca; Santos, Murilo C.; Schwambach, Joséli; Pedrotti, Carine; Delamare, Ana Paula L.
Abstract: Ripe rot is one of the most important bunch diseases of grapes in the highlands of southern Brazil and a matter of concern for winegrowers. Sixty‐one strains isolated from berries of Vitis labrusca and V . vinifera varieties with symptoms were classified by phylogenetic analysis of the sequences of β‐tubulin, glyceraldehyde‐3‐phosphate dehydrogenase, D1/D2 domain of 28S rDNA, and rDNA internal transcribed spacer. They were also characterized by morphology, and their pathogenicity was evaluated. The combined molecular data allowed identification of six Colletotrichum species: C . fructicola, C . kahawae and C . viniferum (gloeosporioides complex), C . limitticola, C . nymphaeae (acutatum complex), and C . karstii (boninense complex). This is the first report of C . karstii and C . limitticola associated with the ripe rot of grapes. Morphological characteristics varied within and among species, confirming their separation at the complex level. Pathogenicity tests on V . vinifera berries showed that the most prevalent species, C . viniferum (37.8%) and C . fructicola (36.1%), were more virulent than the less prevalent species C . limitticola and C . karstii . Our findings indicate that there is a high diversity of Colletotrichum species associated with ripe rot disease of grapes in Brazil. There were no clear differences in the distribution of Colletotrichum species between V . labrusca and V . vinifera varieties. The determination of fungal species responsible for grape ripe rot in Brazilian vineyards may contribute to further epidemiological studies and the development of more efficient prophylactic methods for ripe rot management. Abstract : C. fructicola and C. viniferum are the most prevalent species on grape ripe rot in southern Brazil. C. kastii and C. limitticola were first associated with this disease. Colletotrichum species did not differ between Vitis species.